DEIXIS IN THE SPIDERWICK CHRONICLES MOVIE SCRIPT - Mira Ardeatika; Melyy Nurmala Setiawan (IKIP Siliwangi, 2019)
Pragmatics is the study of the relationship between language and context that forms the basis of determining understanding of utterance. This study was entitled “An Analysis of deixis in The spider wick chronicles script”. The problems of this study were what types of deixis are used in the spider wick chronicles script, and what is the dominant deixis used in The Spider wick Chronicles movie script. The objectives of this study were to find the types of deixis and to find the dominant of deixis in The spider wick Chronicles movie script. This study was purposed to find out the types and the dominant of deixis are used in The spider wick chronicles script. The script was get from internet. This study applied descriptive qualitative method. The following steps, it applied was the first, this study looked for the movie, the second, this study watched the movie, then, looked for the movie script of the movie “The spider wick chronicles”, the fourth, this study identified the sentence of the movie script based on four types of deixis. From the analysis, it is found that there are four types : personal deixis, time deixis, place deixis, and discourse deixis. Keywords: Pragmatic, deixis, the spider wick chronicles script.